The Relational Materiality of Groundwater. Issue 1 (1st June 2021) - Powis, Anthony
Abstract : This paper is part of a larger research project which draws out ways of knowing and thinking with groundwater from Chennai, south India. The (under)ground or (sub)terranean environment is a thick and complex, three-dimensional space of "nothing but change, " but whose utility is essential to sustaining urban life above it. This paper looks at multiple, specific, and contradictory ways in which the materiality of groundwater is understood and intervened in. Using the case of the ongoing Chennai Metro Rail construction project, and its disciplinary cultures of representation, I bring attention to the ground and its waters as a composite system in both balance and unrest, and an active, vital component of the city. Through unpacking established concepts of strata, porosity, and pressure, I will cast groundwater not as an objective fact, always pictured by, and relative to, a human subject, but as an actual being which humans (and others beyond) perceive, relate to, and come into contact with. I close by drawing from this account a possible further set of concepts which groundwater generates—dynamic states which are common to human and material life—suggesting that a relational theory of groundwater materiality, based on leaking as opposed to bordering, might better respond to the ways in which groundwater troubles knowledge.